Ασυνέχειες ή συνέχειες της ελληνικής νομικής γλώσσας (1974-2014) - Gortych-Michalak, Karolina (My University, 2015)
Languages for Specific Purposes (LSPs) such as Legal Language are parts of national languages. They may be deemed parts of language systems because they are based on certain national, general linguistic grammar and they have become mutually intermingled. Even specific terms used in the frame of a certain LSP is created on the basis of the grammatical rules of the general language; thus one cannot deem legal language may not be considered to be an isolated, independent language. Moreover, even from a functional point of view legal language has rules correlated with its general language as they both describe a certain reality and are used for linguistic communication. Obviously Legal language and other LSPs refer to various realities and specific communicational situations, but their general functions are the same as the functions of the general, ethnic language. These assumptions lead to the conclusion that as any ethnic language can be investigated for their continuity and discontinuity, so LSPs within this general language can be investigated the same way. Moreover such investigations can enrich the knowledge of changes in the specific ethnic language. The study is intended to present the parametric method for investigating the phenomena of continuity and discontinuity from the diachronic (historical) point of view. When examining certain patterns of Greek legal languages the interdisciplinary approach is needed. Thus the investigation is based on linguistic and legal arts and methodology. The investigation is a comparative study based on two groups of textual corpuses. The corpuses are legislative acts (constitutions, laws, decrees), which have been changed during the period 1974-2014. The linguistic and legal-linguistic phenomena are investigated using a comparative criterion. The parameterisation then enables provision of the third element of the comparison "tertium comparationis", which is a set of relevant dimensions. As methodology has an interdisciplinary character thus the results throw new light not only on linguistics, but also on jurisprudence and social sciences. When discussing the results, some fields of application for the results are given.
Continuities or discontinuities in Greek legal language (1974-2014)
Keywords: Greek language; Greek legal anguage; legal linguistics; historical linguistics; historical cpomparative studies; Greek for Specific Purposes; LSP; linguistic parammeterrizastion